A Low Power Voltage Sag Compensator - Martinz, Fernando O.; Galassi, Mauricio; Giaretta, Antonio R.; Oliveira, Marco A.; Silva, Fabiana A.T.; Masuda, Mario; Copeliovitch, Simão; Zanetti, Eric R.; Lima, Eduardo G.; Camargo, Josué; et al. (Eletrônica de Potência, 2006)
The increasing use of voltage variation sensitive loads in industrial applications nowadays has brought a real concern about interruption costs and damages in complex production lines. This paper presents a power-electronic–based device which compensates voltage sags, restoring the load voltage to acceptable values through a series connected injection transformer. The ratings and power requirements of a low-power voltage sag compensator, also known as Dynamic Voltage Restorer (DVR) are derived, as well as its deadbeat control algorithm implemented in a Digital Signal Processor (DSP). Finally, simulation and experimental results of a 5-kVA prototype are presented.